1991
DOI: 10.3758/bf03199567
|View full text |Cite
|
Sign up to set email alerts
|

The role of language familiarity in voice identification

Abstract: Four experiments examined the effects of language characteristics on voice identification. In Experiment 1, monolingual English listeners identified bilinguals' voices much better when they spoke English than when they spoke German. The opposite outcome was found in Experiment 2, in which the listeners were monolingual in German. In Experiment 3, monolingual English listeners also showed better voice identification when bilinguals spoke a familiar language (English) than when they spoke an unfamiliar one (Span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
183
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(208 citation statements)
references
References 14 publications
(22 reference statements)
21
183
0
1
Order By: Relevance
“…Recent studies suggest a relationship between knowing a language and ability to identify talkers in that language (Goggin et al, 1991;Johnson et al, 2011;Perrachione et al, 2011;Sullivan and Schlichting, 2000;Winters et al, 2008). This radically departs from a viewpoint that speech processing operates over an abstract set of symbols.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent studies suggest a relationship between knowing a language and ability to identify talkers in that language (Goggin et al, 1991;Johnson et al, 2011;Perrachione et al, 2011;Sullivan and Schlichting, 2000;Winters et al, 2008). This radically departs from a viewpoint that speech processing operates over an abstract set of symbols.…”
Section: Introductionmentioning
confidence: 92%
“…Perrachione et al (2011) found that individual dyslexic listeners' degree of impairment in phonological processing predicts their ability to recognize voices in their native language. Goggin et al (1991) demonstrated that monolingual English speakers identified English-German bilinguals' voices better when those individuals spoke English than when they spoke German (see also Winters et al, 2008). On the other hand, Goggin et al observed no significant difference in voice recognition abilities for English-Spanish bilinguals who were tested on Englishvs.…”
Section: Evidence For Interaction Between Speech Processing and Talkementioning
confidence: 99%
“…To test this hypothesis, we designed an experiment in which we tried to eliminate linguistic information as much as possible. In an additional experiment, Goggin et al (1991) showed that distortion of the stimulus material severely affects speaker recognition. They used four different types of materials -i.e., normal text passages, mixed words, mixed syllables, and reversed speech -and found that the proportion of correct responses decreased as the passages became progressively more incomprehensible.…”
Section: Methodsmentioning
confidence: 99%
“…They used four different types of materials -i.e., normal text passages, mixed words, mixed syllables, and reversed speech -and found that the proportion of correct responses decreased as the passages became progressively more incomprehensible. Goggin et al (1991) only tested English-dominant listeners. In other words, they did not test whether the foreign-language effect in SIO disappears when the materials become incomprehensible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation